2019
DOI: 10.1002/mgg3.956
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment in young children with fragile X syndrome

Abstract: BackgroundMetformin is a drug commonly used in individuals with type 2 diabetes, obesity, and impaired glucose tolerance. It has a strong safety profile in both children and adults. Studies utilizing the Drosophila model and knock out mouse model of fragile X syndrome (FXS) have found metformin to rescue memory, social novelty deficits, and neuroanatomical abnormalities. These studies provided preliminary evidence that metformin could be used as a targeted treatment for the cognitive and behavioral problems as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 49 publications
0
41
0
1
Order By: Relevance
“…ELS has several potential advantages compared to typical norm-referenced standardized tests [30], such as the Receptive and Expressive subscales of the Mullen Early Scales [37], the Peabody Picture Vocabulary Test-4th edition [38], the Preschool Language Scale-5 [39], the Clinical Evaluation of Language Fundamentals [40], and the Comprehensive Assessment of Spoken Language [41], all of which have been used in clinical trials for FXS [42][43][44][45]. First, ELS interactive contexts are more closely aligned with performance in real-world contexts, and thus, performance is more likely to be generalizable to activities that are functional and meaningful for the individual [46].…”
Section: Expressive Language Samplingmentioning
confidence: 99%
“…ELS has several potential advantages compared to typical norm-referenced standardized tests [30], such as the Receptive and Expressive subscales of the Mullen Early Scales [37], the Peabody Picture Vocabulary Test-4th edition [38], the Preschool Language Scale-5 [39], the Clinical Evaluation of Language Fundamentals [40], and the Comprehensive Assessment of Spoken Language [41], all of which have been used in clinical trials for FXS [42][43][44][45]. First, ELS interactive contexts are more closely aligned with performance in real-world contexts, and thus, performance is more likely to be generalizable to activities that are functional and meaningful for the individual [46].…”
Section: Expressive Language Samplingmentioning
confidence: 99%
“…Neurotransmission is fundamental for brain functions, and defects in neurotransmission are implicated in many neurological disorders, such as AD, FXS, depression and so on. Met has been suggested to be effective in these disorders [ 8 , 9 , 10 , 29 , 30 ]. Although Met exerts its glucose level-lowering effects in the peripheral system, it has been reported that Met can cross the brain–blood barrier rapidly [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a fragile X syndrome (FXS) mouse model, Met treatment ameliorated social deficit, repetitive behavior and abnormal dendritic spine morphology and exaggerated long-term depression (LTD) [ 7 ]. Furthermore, improvements in language and cognitive behaviors were observed in a small sample size of Met-treated FXS patients [ 8 , 9 , 10 ]. In some Alzheimer’s disease (AD) mice models, Met attenuated amyloid plaque deposition and improved learning and memory [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…injection of metformin corrects core de cits, like social de cit, repetitive behavior, abnormal dendritic spine morphology and exaggerated long term depression (LTD) [43]. And there are language, cognitive and behavioral improvements in a small sample size of metformin treated FXS patients [44][45][46]. In an Alzheimer's disease (AD) mice model, metformin attenuates amyloid plaque deposition and spatial memory de cit [47].…”
Section: Discussionmentioning
confidence: 99%